Preferential solvation of acetaminophen in ethanol + water solvent mixtures according to the inverse kirkwood-buff integrals method (2013)
The preferential solvation parameters, i.e., the differences between the local mole fraction of solvents around the solute and those for the bulk co-solvent mixtures in solutions of acetaminophen in ethanol + water binary mixtures were derived from their thermodynamic properties by means of the inverse Kirkwood-Buff integrals (IKBI) method. It is found that acetaminophen is sensitive to solvation effects, so the preferential solvation parameter δxE,A, is negative in water-rich and ethanol-rich mixtures but positive in co-solvent compositions from 0.24 to 0.73 in mole fraction of ethanol. It is conjecturable that in water-rich mixtures the hydrophobic hydration around the aromatic ring and methyl group present in the drug plays a relevant role in the solvation. The more solvation by ethanol in mixtures of similar co-solvent compositions could be due mainly to polarity effects. Finally, the preference of this drug for water in ethanol-rich mixtures could be explained in terms of the bigger acidic behavior of water molecules interacting with the hydrogen-acceptor groups present in acetaminophen such as the carbonyl group.